PYROPHOSPHATE ARTHROPATHY IS A RHEUMATOLOGICAL ICEBERG SYNDROME: TIME TO REASSESS ITS IMPORTANCE IN JOINT DISEASES - Viktoria Georgiyevna Barskova; A E Ilyina; L A Semenova; S G Radenska-Lopovok; M A Osipyants; A V Smirnov; M A Makarov (Современная ревматология)
The paper provides the present views of the epidemiology, pathogenesis, diagnosis, and classification of pyrophosphate arthropathy (PPA). It describes a morphological study of the structure of the knee joint after total prosthetics in a patient diagnosed as having osteoarthrosis. Reasons for low detection rates of the disease are considered. Difficulties in the laboratory and instrumental diagnosis of PPA are analyzed in detail.